2016
DOI: 10.1186/s12982-015-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling subject-specific childhood growth using linear mixed-effect models with cubic regression splines

Abstract: BackgroundChildhood growth is a cornerstone of pediatric research. Statistical models need to consider individual trajectories to adequately describe growth outcomes. Specifically, well-defined longitudinal models are essential to characterize both population and subject-specific growth. Linear mixed-effect models with cubic regression splines can account for the nonlinearity of growth curves and provide reasonable estimators of population and subject-specific growth, velocity and acceleration.MethodsWe provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…This study had limitations: the median time from death to VA was slightly longer than the ideal three months that some recommend, but was well within the maximum 12 months recommended by WHO and was therefore considered unlikely to have had a substantial effect on VA-generated estimates [78,79]; physicians who reviewed clinical and VA data were aware that most decedents were likely HIV-positive and had been enrolled into TB-focused studies, which may have led to greater assignment of HIV- and TB-related CoD; missing operational and research data may have affected consistency of the reference standard; pathological autopsy data were available for a small number of decedents; and, although the reference CoD assigned represent our best estimates using the data available, the true CoD may still differ. Questions on ART and TB treatment, added to the VA instrument by the study team, may have led to changes in how events were reported in the free narrative section; the answers to the questions themselves, however, were not provided to reviewing physicians or to either software.…”
Section: Discussionmentioning
confidence: 99%
“…This study had limitations: the median time from death to VA was slightly longer than the ideal three months that some recommend, but was well within the maximum 12 months recommended by WHO and was therefore considered unlikely to have had a substantial effect on VA-generated estimates [78,79]; physicians who reviewed clinical and VA data were aware that most decedents were likely HIV-positive and had been enrolled into TB-focused studies, which may have led to greater assignment of HIV- and TB-related CoD; missing operational and research data may have affected consistency of the reference standard; pathological autopsy data were available for a small number of decedents; and, although the reference CoD assigned represent our best estimates using the data available, the true CoD may still differ. Questions on ART and TB treatment, added to the VA instrument by the study team, may have led to changes in how events were reported in the free narrative section; the answers to the questions themselves, however, were not provided to reviewing physicians or to either software.…”
Section: Discussionmentioning
confidence: 99%
“…(), Grajeda et al . () and Song ()), local polynomial regression (Gasser and Müller, ; Fan and Gijbels, ) or weighted sequences or quotient differences of the observed data (Müller et al ., ; Härdle, ; De Brabanter et al ., ; Wang and Lin, ; Dai et al ., ; Charnigo et al ., ; De Brabanter and Liu, ). Thus, one approach to estimate derivative curves in a hierarchical setting would be to apply one of the methods that were previously listed independently for each subject.…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason for this is that f .1/ is rarely (if ever) directly measured, introducing complexities that are associated with modelling and estimating f .1/ that do not exist for f (Ramsay and Silverman, 2005). Although sparse, the literature contains methods for estimating a single f .1/ that are based on splines (see, for example, Ramsay and Silverman (2005), Sangalli et al (2009), Grajeda et al (2016 and Song (2016)), local polynomial regression (Gasser and Müller, 1984;Fan and Gijbels, 1996) or weighted sequences or quotient differences of the observed data (Müller et al, 1987;Härdle, 1999;De Brabanter et al, 2011Wang and Lin, 2015;Dai et al, 2016;Charnigo et al, 2011;De Brabanter and Liu, 2015). Thus, one approach to estimate derivative curves in a hierarchical setting would be to apply one of the methods that were previously listed independently for each subject.…”
Section: Introductionmentioning
confidence: 99%
“…() Both approaches are parametric and are not designed to account for subtle or strong departures from the assumed parametric trends. This problem can manifest in a number of ways in longitudinal data, including autocorrelation in the residuals of random intercept/slope models . To address such challenges, one may consider using methods for functional data, which allow more flexible modeling of subject‐specific random curves.…”
Section: Introductionmentioning
confidence: 99%
“…This problem can manifest in a number of ways in longitudinal data, including autocorrelation in the residuals of random intercept/slope models. 5 To address such challenges, one may consider using methods for functional data, which allow more flexible modeling of subject-specific random curves. A random functional intercept model can be understood as a special case of a broader class of models referred to as functional mixed effects models.…”
Section: Introductionmentioning
confidence: 99%